Influence of Extraction Method and Production Area on Antioxidant Content (Phenolic Compounds and ?-Tocopherol) in Virgin Olive Oil from Iran, Greece and Italy - Nasollah Zadeh, Azin; Tayefe, Mandana; Shariffar, Asghar (Asian Journal of Chemistry, 2010)
In this paper, the effects of the production area and extraction method (traditional and modern process) on virgin olive oil quality were studied . The analysis of α-tocopherol contents in samples appeared that the production area was a critical variable, since this compound of olive oil can vary considerably from area to area. On the other hand, it is also concluded that extraction method affected the presence phenolic compounds.